2008
DOI: 10.4049/jimmunol.180.7.4366
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Autoimmune Disease in Day 3 Thymectomized Mice Is Actively Controlled by Endogenous Disease-Specific Regulatory T Cells

Abstract: Female B6AF1 mice thymectomized on day 3 (d3tx) develop autoimmune ovarian disease (AOD) and dacryoadenitis. It has been hypothesized that d3tx breaks tolerance by depleting late ontogeny regulatory T cells (Treg). We now report that Treg greatly expand over effector T cells in d3tx mice and adoptively suppress autoimmune disease in d3tx recipients. In the d3tx donors, Treg from ovarian lymph nodes (LN) preferentially suppress AOD and Treg from lacrimal gland LN preferentially suppress dacryoadenitis, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 23 publications
9
65
0
Order By: Relevance
“…Our results confirm those published by Bandeira and colleagues (21) showing that CD4 ϩ CD25 ϩ Tregs from 3dTx mice can inhibit inflammatory bowel disease, and more recently by Tung and colleagues (34) showing the presence of functional Tregs in a model of thymectomy-induced oophoritis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results confirm those published by Bandeira and colleagues (21) showing that CD4 ϩ CD25 ϩ Tregs from 3dTx mice can inhibit inflammatory bowel disease, and more recently by Tung and colleagues (34) showing the presence of functional Tregs in a model of thymectomy-induced oophoritis.…”
Section: Discussionsupporting
confidence: 82%
“…Actually, all immunodeficient recipients that received CD25-depleted LN cells from gastritic donors showed signals of severe disease, while only 60% of recipients receiving total LN from gastritic donors showed gastritis with parietal cell destruction. This viewpoint is supported by recent data showing that Treg depletion in adult B6AF1 3dTx mice results in a much severe oophoritis (34).…”
Section: Discussionsupporting
confidence: 77%
“…These data suggested that the enhanced proliferative capacity of CD4 + T cells in a Th1-dominant autoimmune setting may overcome a deficiency of direct action of TSLP on CD4 + T cells. In adult NTx mice, CD4 + Foxp3 + Tregs were observed in the periphery, as described (7)(8)(9). We also found that 12-wk-old NTx-TSLPR 2/2 mice had a number of CD4 + Foxp3 + Tregs in the periphery, comparable to those found in NTx-TSLPR +/+ mice (data not shown).…”
Section: Discussionsupporting
confidence: 70%
“…NTx mice possess disease-relevant CD4 + CD25 + regulatory T cells (Tregs), but these Tregs cannot fully prevent autoimmune disease development (7)(8)(9). Adult NTx mice frequently develop AIG, showing lymphocytic infiltration with selective loss of parietal and chief cells from the gastric mucosa, as well as production of autoantibodies to parietal cells (10).…”
mentioning
confidence: 99%
“…[22][23][24] Administration of PC61 (300 g intravenously) significantly decreased (approximately 50%) spleen, kidney, and blood Tregs 5 d after injection compared with mice treated with control IgG (300 g intravenously; Figure 1, A through E). This dosing strategy was chosen on the basis of the kinetic analysis of single-dose PC61 on FoxP3 ϩ Tregs in C57Bl/6 mice.…”
Section: Antibody-mediated Treg Depletion Potentiates Kidney Irimentioning
confidence: 99%